Technoeconomic analysis: the potential and opportunities of transforming Saudi Arabian scrap tires into synthetic fuel via vacuum pyrolysis - Yahya, Sulaiman Al; Omar, Muhammad Mubashar (Frontiers in Energy Research, 2024)
Environmental hazards linked with scrap tires have been a great concern for the Saudi government. The Kingdom of Saudi Arabia has a Vision 2030 project with an aim to produce 50% of its energy through renewable energy resources. The tire market in the country reached 22.2 million units in 2022 and is expected to increase up to 24.9 million in 2028 with a growth rate of 2.11%. This study used a vacuum pyrolyzer for transforming scrap tires into tire-derived oil (TDO), along with other products such as synthesis gas (syngas) and carbon black. It provides a feasible way of transforming scrap tires into synthetic fuel via vacuum pyrolysis (a thermochemical approach). Vacuum pyrolysis of scrap tires at temperature 350–400oC yields 45%–55% derived oil, 10%–15% steel wires, 30%–35% carbon black, and 10%–15% non-condensable gases. The heating value of the obtained tire-derived oil is 32–37 MJ/kg, which is somehow less than that of diesel, which has an energy value of 44–46 MJ/kg. Such products are expected to be obtained after the successful adaptation of advanced techniques such as thermochemical approaches and can successfully be used as an alternative to fossil fuels. Based on the scrap tire produced in the country, if Saudi Arabia can process 22.2 million units of tires (trucks and passenger cars) annually through vacuum pyrolysis, it can earn approximately 47.40 million annually (or 2.14 per tire) through tire pyrolysis. Utilization of carbon black (recovered from scrap tire pyrolysis) in manufacturing tires can save approximately 2.5 tons of CO2 production compared to per ton production of new (virgin) carbon black. This study suggested pyrolysis to be a viable recycling and waste tire management technique, and it can be an independent profitable operation in Saudi Arabia and helps in meeting the Saudi Vision 2030.